The boundedness of Caldern-Zygmund operators by wavelet characterization - Hung, Cheng-Cong; Lee, Ming-Yi (My University, 2012)
This article deals with the boundedness properties of Caldern-Zygmund operators on Hardy spaces (a"e ). We use wavelet characterization of (a"e ) to show that a Caldern-Zygmund operator with *1 = 0 is bounded on (a"e ), is the regular exponent of kernel of . This approach can be applied to the boundedness of operators on certain Hardy spaces without atomic decomposition or molecular characterization.
Keywords: Calderon-Zygmund operators; Hardy spaces; para-product operators